1999
DOI: 10.1046/j.1365-2117.1999.00086.x
|View full text |Cite
|
Sign up to set email alerts
|

Partitioning of intermontane basins by thrust‐related folding, Tien Shan, Kyrgyzstan

Abstract: Well‐preserved, actively deforming folds in the Tien Shan of Kyrgyzstan provide a natural laboratory for the study of the evolution of thrust‐related folds. The uplifted limbs of these folds comprise weakly indurated Cenozoic strata that mantle well‐lithified Palaeozoic bedrock. Their contact is a regionally extensive unconformity that provides a persistent and readily traceable marker horizon. Based on the deformation of this marker, preserved fold geometries support simple geometric models for along‐strike g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
191
1
4

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(201 citation statements)
references
References 57 publications
(75 reference statements)
5
191
1
4
Order By: Relevance
“…The Tianshan extends laterally over $2000 km with active thrusting occurring on both sides and within the belt [Avouac et al, 1993;Burbank et al, 1999;Burchfiel et al, 1999;Thompson et al, 2002]. Along the central southern Tianshan, deformation has propagated into the Tarim basin except in the Aksu reentrant (Figure 1a), where a drastic change in stratigraphy occurs.…”
Section: Regional Frameworkmentioning
confidence: 99%
“…The Tianshan extends laterally over $2000 km with active thrusting occurring on both sides and within the belt [Avouac et al, 1993;Burbank et al, 1999;Burchfiel et al, 1999;Thompson et al, 2002]. Along the central southern Tianshan, deformation has propagated into the Tarim basin except in the Aksu reentrant (Figure 1a), where a drastic change in stratigraphy occurs.…”
Section: Regional Frameworkmentioning
confidence: 99%
“…This latter study also suggest that the recent outspoken uplift of the Tien Shan could be the result of a marked increase in horizontal compressive forces following the abrupt rise of the Tibetan Plateau, as proposed by England and Houseman (1989). Apatite fission-track thermochronology, structural modelling and magnetostratigraphy in the Kyrgyz Range (and adjoining ranges) and the Chu Basin in the northern Kyrgyz Tien Shan further showed that a first strong phase of rock uplift and deformation affected the northern Tien Shan 10-11 Ma ago, and a second accelerated phase occurred 5-3 Ma ago [Burbank et al 1999;Bullen et al, 2001;De Grave et al, 2004;Sobel et al, 2006]. The latter acceleration is also expressed in the stratigraphy by a marked change in sedimentary environment in the Late Pliocene-Early Pleistocene: thick sequences of coarse conglomerates, sedimentary gaps and tectonic unconformities are observed [Cobbold et al, 1994;Abdrakhmatov et al, 2001].…”
Section: Problem Solutionmentioning
confidence: 98%
“…However in most cases, it is safe to say that cooling initiated, seemingly in a somewhat poly-phased fashion, during the last 10 to 15 Ma. These cooling curves in the models might thus represent the timing of the denudation of the modern Tien Shan orogenic edifice and can be corroborated by several lines of independent geological evidence from such fields as sedimentology [Cobbold et al, 1994;Métivier & Gaudemer, 1997;Dill et al, 2007], magneto-stratigraphy [Sun et al, 2004;Charreau et al, 2005;Huang et al, 2006;Ji et al, 2008], geomorphology and structure [Tibaldi et al, 1997;Yin et al, 1998;Burbank et al, 1999;Abdrakhmatov et al, 2001;Thompson et al, 2002;Buslov et al, 2003;Fu et al, 2003;Hubert-Ferrari et al, 2007;Oskin & Burbank, 2007], geophysics [Trapeznikov et al, 1997;Bielinski et al, 2003;Rybin et al, 2004;, geodesy [Abdrakhmatov et al, 1996;Reigber et al, 2001;Vinnik et al, 2004;Tychkov et al, 2008], and other geochronological studies [Sobel & Dumitru, 1997;Bullen et al, 2001;Sobel et al, 2006;De Grave et al, 2007a;Heermance et al, 2007]. We should caution the reader that this Late Cenozoic feature is mainly obtained by modelling the AFT data [Laslett et al, 1987;Ketcham et al, 2000].…”
Section: Termochronologymentioning
confidence: 99%
“…The close association of the Fergana Basin with the Talas -Fergana Fault resulted in the development of a basin morphology that differs from that of other Cenozoic-age intramontane basins within the Tien Shan typically bounded by north-or southverging faults (e.g. Cobbold et al 1996;Burbank et al 1999;Macaulay et al 2014). The Fergana Basin is located due north of the Pamir, suggesting a possible tectonic link between indentation of the latter and basin evolution.…”
Section: Fault Reactivation and Far-field Effectsmentioning
confidence: 99%
“…The Jurassic -Cretaceous was characterized by a general planation of the previously formed relief (e.g. Makarov 1977;Chediya 1986;Burbank et al 1999;Allen et al 2001;Cunningham et al 2003;Jolivet et al 2010Jolivet et al , 2013Jolivet et al , 2015, providing sediments to these newly forming extensional basins (Brookfield & Hashmat 2001;Klett et al 2006;Fü rsich et al 2015;Brunet et al 2017).…”
Section: Geological Evolution Of Central Asian Basins and The Westernmentioning
confidence: 99%